Angel Investors : Do They Clone or Contrast? - Annamalaisami, Niroopa Rani; Kuruva, Ramesh; Annamalai, Thillai Rajan (Indian Journal of Finance, 2022)
The aim of this study is to analyse and compare the nature, behaviour and investment preferences of angel investors around the world. In order to get a better understanding of the emerging economies, a special emphasis was given on the Indian Angel market. Angel investors’ detailed characterization and their investment preferences identified in this paper would help entrepreneurs fine-tune their fundraising strategies. Furthermore, this paper highlighted some key differences in angel investment trajectories in different economies. The transparent and mature angel markets encourage angel investors from diverse age groups, gender and educational backgrounds to participate actively. And the scattered angel investors in developed economies making diversified investments stimulate start-ups’ balanced growth, both geographically and across all sectors. The findings show that there is significant heterogeneity among angel investors in emerging and developed economies that can be attributed to structural, economic, institutional, legal, and cultural differences between different economies. These findings would help policymakers promote a balanced and robust start-up ecosystem that facilitates angel investors’ active participation and the resulting magnificent growth of entrepreneurship and economy.